Pigmented Bowen's disease presenting with a "starburst" pattern - Maione Vincenzo; Enzo Errichetti; Sara Laurent Roussel; Celeste Lebbé (Mattioli1885, 2016)
Pigmented Bowen's disease (pBD) is an uncommon in situ squamous cell carcinoma of the skin usually presenting as a dark scaly plaque involving chronically exposed sites, which is not uncommonly mistaken for other similar pigmented lesions, such as melanoma, pigmented basal cell carcinoma or seborrheic keratosis [1,2]. Dermoscopy has been proven to improve its diagnosis by showing several findings, i.e., gray/brownish dots in linear arrangement, scales, coiled vessels, focal/multifocal amorphous hypopigmentation and bluish structureless areas [1,2]. However, pBD may sometimes display dermoscopic features which are typical of other pigmented lesions, thus making its recognition quite troublesome despite the use of dermoscopy [1,2]. We report a case of pBD with a "starburst" pattern, discussing its dermoscopic differential diagnosis.